The influence of birth season on height: Evidence from Indonesia - Sohn, Kitae (Wiley-Liss, Inc, 2015)
© 2015 Wiley Periodicals, Inc.Objectives: Literature on the effect of birth month on height has generally considered regions in temperate climates. However, because many climatic conditions there change with seasons, it is difficult to isolate potential causes. This study estimated the effect of birth month and season on terminal height by analyzing the population of a country with only a few factors driving its climate. Materials and Methods: The sample was derived from nationally representative data of the Indonesian population. We considered 9,262 men and 10,314 women 20-50 years of age. We applied cosinor analysis to a time series of height by birth month. We then applied a more flexible approach by regressing height on a series of dummy variables for birth month (and, subsequently, season) and birth year fixed effects by sex. Results: There was no statistically significant difference in height by birth month. However, although weakly significant, men born in the dry season (June-September) were 2.3 mm shorter than those born in the wet season (the remaining months). The corresponding figure for women was 2.6 mm, a statistically significant difference. Discussion: We eliminated some potential factors previously suggested in the literature, including insolation, the position of our planet with respect to the sun, food availability, and maternal workload. We speculate that babies born in the dry season were affected in the third trimester by the high disease burden that characterizes the wet season.